2018
DOI: 10.5751/es-09821-230113
|View full text |Cite
|
Sign up to set email alerts
|

Supplying the wildlife trade as a livelihood strategy in a biodiversity hotspot

Abstract: ABSTRACT. Much of the global wildlife trade is sourced from biodiversity-rich developing countries. These often have high levels of poverty and habitat loss, particularly in rural areas where many depend on natural resources. However, wildlife collection may incentivize local people to conserve habitats that support their livelihoods. Here we examined the contribution of the commercial collection of live animals to rural livelihoods in Madagascar, one of the world's most important biodiversity hotspots. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
(35 reference statements)
0
31
0
Order By: Relevance
“…For example, a small amount of money will go further amongst local collectors, compared with intermediaries and exporters residing in towns and cities, and local collectors in rural communities may be more in need of employment no matter how small the financial benefits. Recent research in the same study area (Robinson et al 2018) revealed that 13% of households in collection areas benefitted from local harvest of live animals for export (including some of the poorest) and it was potentially profitable. However, it also revealed the unreliable and sporadic nature of live animal collection (limited by quotas, season, opportunity cost and supply), and that incentives appear insufficient to promote conservation of species and habitats (Robinson et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, a small amount of money will go further amongst local collectors, compared with intermediaries and exporters residing in towns and cities, and local collectors in rural communities may be more in need of employment no matter how small the financial benefits. Recent research in the same study area (Robinson et al 2018) revealed that 13% of households in collection areas benefitted from local harvest of live animals for export (including some of the poorest) and it was potentially profitable. However, it also revealed the unreliable and sporadic nature of live animal collection (limited by quotas, season, opportunity cost and supply), and that incentives appear insufficient to promote conservation of species and habitats (Robinson et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research in the same study area (Robinson et al 2018) revealed that 13% of households in collection areas benefitted from local harvest of live animals for export (including some of the poorest) and it was potentially profitable. However, it also revealed the unreliable and sporadic nature of live animal collection (limited by quotas, season, opportunity cost and supply), and that incentives appear insufficient to promote conservation of species and habitats (Robinson et al 2018). Equally, in their study of mantella frog trade in Madagascar, Rabemananjara (2008) observed that because collection permits are issued to exporters rather than local collectors -and collectors are paid low prices -the system becomes counterproductive in terms of promoting sustainable harvesting and incentives to conserve resources based on benefits received.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations